Biomechanical Characterization at the Cell Scale: Present and Prospects - Basoli, Francesco; Giannitelli, Sara Maria; Gori, Manuele; Mozetic, Pamela; Bonfanti, Alessandra; Trombetta, Marcella; Rainer, Alberto (Frontiers in Physiology, 2018)
The rapidly growing field of mechanobiology demands for robust and reproducible characterization of cell mechanical properties. Recent achievements in understanding the mechanical regulation of cell fate largely rely on technological platforms capable of probing the mechanical response of living cells and their physico–chemical interaction with the microenvironment. Besides the established family of atomic force microscopy (AFM) based methods, other approaches include optical, magnetic, and acoustic tweezers, as well as sensing substrates that take advantage of biomaterials chemistry and microfabrication techniques. In this review, we introduce the available methods with an emphasis on the most recent advances, and we discuss the challenges associated with their implementation.